2015
DOI: 10.3109/09553002.2016.1115135
|View full text |Cite
|
Sign up to set email alerts
|

The soluble receptor ST2 is positively associated with occupational exposure to radiation

Abstract: Purpose Radiation exposure, besides the risk of cancer, may also increase the risk of non-cancer diseases, including cardiovascular disease (CVD). This study investigates whether the soluble form of the ST2 receptor (sST2), an emerging prognostic marker in patients with CVD, can be used to monitor the CVD risk in individuals occupationally exposed to radiation. Materials and methods sST2 in blood plasma from 69 individuals, 45 workers from the nuclear industry and 24 controls, was analyzed using enzyme-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In heart failure patients and in population-based studies, elevated levels were associated with increased mortality [ [11] , [12] , [13] , [14] , [15] , [16] ]. No studies on the effect of RT alone exist, but radiation exposure was associated with increased ST2 levels in nuclear plant workers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In heart failure patients and in population-based studies, elevated levels were associated with increased mortality [ [11] , [12] , [13] , [14] , [15] , [16] ]. No studies on the effect of RT alone exist, but radiation exposure was associated with increased ST2 levels in nuclear plant workers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Malekirad et al (2005) and Kumar et al (2016) found the TAS value to be higher in radiology unit workers. Katsarska et al (2016) and Aneva et al (2019) reported that the TAS value was higher in nuclear power plant workers who were occupationally exposed to gamma radiation compared to the group without radiation exposure. Katsarska et al (2016) also noted high levels of ROS in lymphocytes in the group exposed to radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Heart radiation exposure can lead to vascular endothelial cells damage and vascular inflammatory reaction, finally interstitial ischemic fibrosis caused by thrombosis or inflammatory reaction. A study demonstrated that the sST2 levels in workers from the nuclear industry were significantly higher (5 folds) than control group without exposure history [17] . When patients receive chest radiotherapy, the heart would be exposed to large doses x ray in a short time, especially in central lung tumors and esophageal cancer.…”
Section: Introductionmentioning
confidence: 96%